Proposed Manpower Cuts at United States Air Force Military Treatment Facilities: Concerns and Solutions - Tyrone Anthony McDougald (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
During pandemic events, we experienced heavy burden on our medical labor worldwide. This study too concentrated on the problem of limited medical staff and tackling patient demands, while still keeping motivation up within the workforce. This study aimed to understand concerns and find solutions for 2021 as well as future fiscal years of proposed manpower cuts at United States Air Force Military Treatment Facilities (USAF MTF). A significant pending proposal would cut a shocking 4,684 USAF medical positions worldwide. This study’s purpose was to shield light on employee and stakeholder concerns to provide practical solutions mitigating impacts, maintaining staff productivity, motivation, and job satisfaction. It then prioritized the current healthcare services. Theory and pervious literature indicated manpower cuts lead to social effects by reducing recognition, open communication, and motivation for provider staff as well as reducing productivity and quality care. Human Relations (HR) and Herzberg’s Motivation-Hygiene theories were applied to developing data collection instruments in this qualitative study in order to derive solutions for continued quality care and staff motivation in preparation of manpower cuts. Interviews were conducted with 10 provider staff and 10 USAF consultants then analyzed to inform a focused solution-driven discussion with 10 MTF leaders. Analysis led to focus group findings, which were then summarized to highlight practical solutions and recommendations in areas of manpower, support, resources, innovation, communication and motivation. Key implications for businesses and practitioners found that manpower cuts can become an essential part of any business environment but there are ways to mitigate these effects and stay motivated and productive by focusing on employee’s needs, innovations and prioritizing services.